Effect of blood plasma cryoprecipitate on microflora growth taking into consideration possibilities for its use - V. F. Chernenko; V. G. Lubyansky; A. P. Momot; A. N. Zharikov; A. R. Aliev; N. N. Zvezdkina; D. N. Ustinov (Acta Biomedica Scientifica)
The necessity of use of cryoprecipitate (CP) in clinic as a basis of biocomposite for creation of interstitial barrier to prevent the spread of retroperitoneal abscesses in necrotizing pancreatitis. The research of the influence of CP on the growth of microorganisms with three types of cultures (E. coli, Acinetobacter, E. faeccalis) was realized. Incubation of bacteriological environment (51 series) was carried out under standard conditions in the presence of CP, antibiotics and retroperitoneal adipose tissue with a visual assessment in vitro and by the change of the densitometric density of environments on the MicroScan Turbidity Meter (Siemens) unit. As it was stated, the presence of CP in pure form in bacteriological environment as well together with an antibiotic or adipose tissue does not affect the growth of investigated microflora and in combination with the antibiotic inhibits it suppresses growth. Taking into consideration the indifference of CP to microflora, its use as a drug interstitial barrier to the migration of retroperitoneal phlegmon in necrotizing pancreatitis the activation of abdominal infection is safe.